Effect of Nitrogen, Phosphorus, and Potassium on the Biomass Production of Spirogyra Hyaline - Nadia Jabeen; Rimsha Arshad; Muhammad Hammad Ashraf; Ishrat Fatima (BioScientific Review, 2026)
Background. The current research investigated the effect of nitrogen, phosphorus, and potassium on the biomass production of Spirogyra hyaline Cleve.Methods. Different nitrogen sources [(NH4) SO4, NH4Cl, NaNO3, Ca (NO3)2, and Co (NO3).6H2O] are used for Spirogyra hyaline biomass production. Particularly, 2.0% of Ca (NO3)2 significantly enhanced biomass (18.2 gL-1), the volumetric rate of biomass production (4.7), specific rate of biomass production (2.47), high product yield coefficient (1.74), and specific rate of biomass production (1.54).Results. Among all the phosphorus sources [Na3PO4, (NH4)3PO4 and K2HPO4], K2HPO4 yielded the optimum biomass production (20.4 g L-1), with 0.5 g L-1 resulted in maximum biomass production of 22.4 g L-1. Moreover, from various potassium sources [KNO3, KH2PO4, K2Cr2O7, and KNaC4H4O6], KH2PO4 resulted in significantly high volumetric rate of biomass production (2.1) and specific rate of biomass (3.65), with 0.5g L-1 showing the maximum biomass production of 18.6 g L-1. Further increase in the concentration of nitrogen, phosphorus, and potassium significantly decreased the biomass production. Additionally, when tested in modified and control media, the algal biomass production was gradually increased in both media and reached optimum after 18 days of incubation (13.1 g L-1 and 10.3g L-1 respectively).Conclusion. Therefore, it was concluded that standard media gave better results and was selected for optimum biomass production of Spirogyra hyaline Cleve.